Applying the Central Clearing Mandate : Different Options for Different Markets - Kiff, John (IMF Working Papers; Working Paper ;, 2022)
Back in 2009, G-20 leaders have called for all standardized over-the-counter (OTC) derivatives to be cleared through central counterparties (CCPs). By now, 18 of the 24 Financial Stability Board (FSB) member jurisdictions have provided for mandatory central clearing frameworks in place, covering at least 90 percent of all standardized OTC derivatives in their jurisdictions. However, the authorities in several countries remain confronted with the hows and wherefores of mandatory central clearing, also in light of the international dimension of OTC derivatives contracts. This paper examines the policy options available to countries that have yet to fully conform to the clearing mandate, centered on the setup of local CCPs or on the use of foreign CCPs, and elaborates on their feasibility, risks and benefits from an economic, legal and tax viewpoint.